DYEING AND FINISHING IMPROVEMENT USING SIX SIGMA AT DYEING AND FINISHING TOX TEXTILE - Yohan
TOX textile is textile company in West Java. The company established since 1968, makes fabrics from polyester as raw material. Dyeing and Finishing is a division for processes greige fabrics into finished fabric. Dyeing and Finishing, have problems with fabric production delays. Dyeing and Finishing department have target accuracy of fabric production 95%, but in 2017 they cannot achieve this. The division's production capacity is greater than sales. The characteristics of Dyeing and Finishing processes that depend on many machines and have a vulnerable time. This is because of the many parameters in fabric making and the challenges of this division. The purpose of this study is to find the main cause and propose improvements. The use of Six Sigma using the DMAIC methodology (Define, Measure, Analyze, Improve and Control) expect to improve and optimize existing processes. This methodology can be reference for companies to develop them. After passing through the Define and Measure stages, analysis using the Failure Mode and Effect Analysis (FMEA) method applied to each process that causes problems. Based on FMEA, the use of manual scheduling and unstructured is a failure that has the highest Risk Priority Number. From the results of FMEA, to find out the cause of more detail than the failure mode of use of manual scheduling and unstructured that is using cause and effect diagram. From the results obtained in the analysis phase, the factor that causes it to happen are communication flow, human resources knowledge and skill, planning strategy, and information system. Based on existing problems, a proposed improvement made for the Dyeing and Finishing division. First, Dyeing and Finishing division need to improve communication flow to reduce errors during information distribution and increase the handle of incoming orders. Furthermore, the number of errors and ineffectiveness in work requires this division to improve the human resources capability. Providing training and team building to workers and staff can be a solution to this problem. The use of planning methods that are used results in many problems and is less effective. Because of that, the planner has to make a new strategy by making standards for machine alignment, making tools, and the need to conduct evaluations. Last is the making of information systems that support data retrieval and facilitate monitoring of processes that occur.